Human resource management tools: kaizen concept - Величко, Сергей Александрович; Вайсман, Владислав Александрович (Eastern-European Journal of Enterprise Technologies, 2012)
The application of poorly formalized relationships between subsystems of projects focused on use of human factor, which creates a basis for continuous improvement of organizations and gives creative climate is proposed